284 Gut and Skeletal Muscle Control the Effect of low Protein Diets on Feed Intake and Thermal Radiation of Broilers During Experimentally Induced Heat Stress. (21st September 2022) - Sutton, Julia; Habibi, Mohammad; Shili, Cedrick n; Beker, Ali; Burch-Konda, Jacob; Salak-Johnson, Janeen L; Foote, Andrew P; Pezeshki, Adel
Abstract: The objective of this study was to assess the effects of low protein diets on feed intake (FI), heat production and markers of FI and thermogenesis regulation in broilers under experimentally induced heat stress. Two-hundred-day-old broiler chicks were weight-matched and assigned into 36 pens (5-6 chicks/pen) followed by assigning them into two treatments (18 pens/treatment): 1) thermoneutral (TN), 2) heat stress (HS). Within each treatment, the pens were randomized to receive two diets (9 pens/diet): 1) normal protein (NP), 2) low protein (LP). The study lasted 6 weeks with 2 weeks of acclimation and 4 weeks of data collection. On week 6, birds were euthanized, and blood and tissue samples collected. All data were analyzed with either GLM or mixed procedure (SPSS). The student's t-test was used to separate means between NP and LP diets within each treatment. There was no difference in average daily gain between NP and LP diets in the TN group, but LP decreased that during HS (P< 0.05). In TN condition, LP tended to increase the average daily feed intake (ADFI) compared to NP (P< 0.1), while during HS, LP was not different from NP in terms of ADFI (P>0.05). In TN condition, LP had a higher thermal radiation than NP, but LP had less thermal radiation than NP during HS (P< 0.05). In support of ADFI data, LP had a greater ghrelin transcript in the duodenum than NP in TN condition (P< 0.05). However, during HS, LP tended to decrease the plasma ghrelin concentration compared with NP (P< 0.1). Unlike TN condition, LP had a decreased muscle sirtuin and cytochrome c oxidase transcript than NP during HS (P< 0.05). Our data provide evidence that low protein diets mitigate the negative outcome of heat stress by reducing feed intake and heat production, which are regulated through genes expressed in the gut and skeletal muscle.